2021
DOI: 10.3390/ijms22189679
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ribosomal Protein Synthesis in Mycobacteria: The Autogenous Control of rpsO

Abstract: The autogenous regulation of ribosomal protein (r-protein) synthesis plays a key role in maintaining the stoichiometry of ribosomal components in bacteria. In this work, taking the rpsO gene as a classic example, we addressed for the first time the in vivo regulation of r-protein synthesis in the mycobacteria M. smegmatis (Msm) and M. tuberculosis (Mtb). We used a strategy based on chromosomally integrated reporters under the control of the rpsO regulatory regions and the ectopic expression of Msm S15 to measu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The cytotoxic effects of 4b on bacteria were assessed by MSmeg cellular growth in the presence of the dye at various concentrations since the measurements of bacterial growth rate reflect the concentration of actively growing cells ( 42 ). Рre-cultured MSmeg strains bearing empty pAMYC vector ( 43 ) were diluted in ratio 1:100 with fresh LB medium containing chloramphenicol (34 μg/ml), Tween 80 (0.05%) and 4b at a concentration of 400 nM, 1 μM or without dye (positive control), and grown up at 37°C while shaken at 200 rpm. Then, the optical density of the culture (OD 600 ) until the stationary growth phase was measured ( Supplementary Figure S12 ).…”
Section: Methodsmentioning
confidence: 99%
“…The cytotoxic effects of 4b on bacteria were assessed by MSmeg cellular growth in the presence of the dye at various concentrations since the measurements of bacterial growth rate reflect the concentration of actively growing cells ( 42 ). Рre-cultured MSmeg strains bearing empty pAMYC vector ( 43 ) were diluted in ratio 1:100 with fresh LB medium containing chloramphenicol (34 μg/ml), Tween 80 (0.05%) and 4b at a concentration of 400 nM, 1 μM or without dye (positive control), and grown up at 37°C while shaken at 200 rpm. Then, the optical density of the culture (OD 600 ) until the stationary growth phase was measured ( Supplementary Figure S12 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have examined the rpsO regulation in mycobacteria M. smegmatis ( Msm ) and M. tuberculosis ( Mtb ) and provided evidence for the S15-mediated autoregulation at the translation initiation level [ 163 ]. Remarkably, the autogenous regulation of the mycobacterial rpsO genes appears to strictly require the pseudoknot conformation of the 5′UTR so that mutations disrupting the pseudoknot completely abolish the uS15-mediated translational repression ( Figure 4 ).…”
Section: Moonlighting R-proteins Of the 30s Ribosomal Subunitmentioning
confidence: 99%
“… Mycobacterial uS15 represses its own translation by binding to the pseudoknot structure within the rpsO 5′UTR [ 163 ]. On the left : Predicted secondary structures for the Msm and Msm rpsO 5′UTRs form pseudoknots.…”
Section: Figurementioning
confidence: 99%
“…The work by Aseev et al [ 3 ] concerns the regulation of expression of the rpsO gene, coding for the S15 protein (one of the ribosomal proteins from the small ribosome subunit) in Mycobacterium smegmatis and M. tuberculosis . Using novel genetic tools (constructed by Aseev et al [ 3 ]) they found that regulation of the rpsO gene expression occurs mainly at the translation stage in M. smegmatis and M. tuberculosis , and proceeds according to the negative feedback mode. The formation of the pseudoknot in the rpsO 5′UTR region appeared to be essential for the S15 protein-mediated repression of translation of its own mRNA.…”
mentioning
confidence: 99%